Domain Specific Situated Planning (Student Abstract) - Thomas, Devin Wild (Proceedings of the International Symposium on Combinatorial Search, 2023)
Traditionally when planning we assume that we receive the problem instance as input, then formulate a plan, then the clock begins and the agent executes the plan. Sometimes we are forced to consider time passing as we plan, which is known as situated planning. In my dissertation I explore situated planning in three domains: grid based path planning, the orienteering problem and opportunistic science.